PENGARUH MODEL PEMBELAJARAN FREE INQUIRY TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN MATEMATIKA KELAS III MI BAHRUL ULUM - Zuni Humairoh; Fiki Mi'mar Rifdah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2020)
Learning models are planning to create learning effectively and efficiently. Research focus, to know: a) How to study free inquiry in Madrasah Ibtidaiyah Bahrul Ulum Jombang class III A? b) How is the outcome of students learning MI Bahrul Ulum Jombang class III A? The study used a simple linear regression analysis test and a classic assumption test. This research is a quantitative study of simple regression types. Its population, a total of 718 students, samples of research, using random sampling techniques using probability theory, the sample amounted to 37 students. The research instrument is a poll using a Likert scale. Instruments to collect data in the form of model free inquiry, and student learning results. Analysis of results Using Test-t (T-Test). The results showed that, there is an independent variable influence on dependent variables, from the results of test-t calculations, with the details: a) Learning free inquiry in Madrasah Ibtidaiyah Bahrul Ulum Jombang class III A very good, with the result of 100% achievement. b) The influence of the model of free inquiry towards the outcome of learning outcomes of class III A MI Bahrul Ulum Jombang obtained the value T count = 6.814 that, T count > T table IE 6.814 > 2.021 significant standard/probability value is 0.000 < 0.05 then Ho rejected and Ha accepted